2017
DOI: 10.1186/s12889-017-4651-7
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology of Humanpapilloma virus infection among women in Fujian, China

Abstract: BackgroundHuman papillomavirus (HPV) infection is the main etiological factor for the development of cervical cancer. Here we assessed the prevalence and distribution of HPV genotypes in Fujian population.MethodsA total of 8678 women aging from 17 to 84 years olds were recruited from the Fujian Medical University Union Hospital in Fujian Province. Every woman had a face-to-face interview. Cervical samples were collected from each participant and HPV screening was conducted using microarray hybridization.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 41 publications
(46 reference statements)
3
37
5
Order By: Relevance
“…The HPV infection rate varies markedly in China due to its large population and territory. Our results showed that the prevalent detection of any HPV subtypes among gynecological outpatients in Guangdong was 20.16%, which was higher than HPV prevalence in Hubei (17.68%) and lower than that in Fujian (38.3%) and Zhejiang (22.3%) . Considering the same laboratory method (Chaozhou Hybribio Limited Corporation, Chaozhou, China) in HPV detection among these studies, the diversity in HPV prevalence might mainly be attributed to geographical variation.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…The HPV infection rate varies markedly in China due to its large population and territory. Our results showed that the prevalent detection of any HPV subtypes among gynecological outpatients in Guangdong was 20.16%, which was higher than HPV prevalence in Hubei (17.68%) and lower than that in Fujian (38.3%) and Zhejiang (22.3%) . Considering the same laboratory method (Chaozhou Hybribio Limited Corporation, Chaozhou, China) in HPV detection among these studies, the diversity in HPV prevalence might mainly be attributed to geographical variation.…”
Section: Discussionmentioning
confidence: 57%
“…For example, in Zhejiang province, the main genotypes of HR HPV were HPV16, 52, 58, 53, and 18 . In Fujian province, the main genotypes of HR HPV were HPV16, 52, 58, 53, and 33 . In Hubei province, the main genotypes of HR HPV were HPV 52, 16, 58, 39, and 51 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in different countries and regions, the distribution of HPV genotypes in cervical cancer and precancerous lesion varies was different . Many studies proved that the genotype distribution of HPV differed in the various provinces of China . The most frequent hr‐HPV genotypes were HPV 16 and HPV 58, HPV 52 and HPV 16, HPV 16 and HPV 18, and HPV 16 and HPV 52 in Shanxi, Sichuan, Jiangxi, and Fujian province, respectively.…”
Section: Introductionmentioning
confidence: 99%